EGFR mutation testing of lung cancer patients – Experiences from Vestfold Hospital Trust. (1st February 2016) - Berg, Janna; Fjellbirkeland, Lars; Suhrke, Pål; Jebsen, Peter; Lund-Iversen, Marius; Kleinberg, Lilach; Helgeland, Lars; Brustugun, Odd Terje; Helland, Åslaug
Abstract : Background. Patients with advanced stage lung cancer and somatic mutations in the epithelial growth factor receptor (EGFR) gene are currently treated with tyrosine-kinase inhibitors. The Norwegian Lung Cancer Group (NLCG) recommended EGFR testing of all patients with non-small cell lung carcinoma (NSCLC) from June 2010. From March 2013, testing of squamous cell carcinomas was terminated. We have analysed how these recommendation were followed at a medium-sized Norwegian hospital and we present data on mutation frequency, retesting and possible explanations for missing test results. Material and methods. All pathology reports for patients diagnosed with NSCLC at Vestfold Hospital Trust were examined for the period June 2010 to December 2013. Mutation analyses were done at the Department of Pathology, Oslo University Hospital. Results. Material was sent for EGFR analysis for 256 of the 304 eligible patients diagnosed in the period. Material from 48 patients was never sent for EGFR testing, of which five samples consisted of too few tumour cells. For the rest, no obvious reason for omitting EGFR mutation analyses was identified. During the first six months of our study period, material from 25 of 66 NSCLC patients (38%) was not tested, whereas only six of the 118 patients (5%) in 2013 were not tested. For 34 patients, the first tissue specimen contained too few tumour cells and a new sample was sent for EGFR analyses for 11 of these. EGFR mutation was detected in 7.1% of the analysed NSCLC and in 9.4% of adenocarcinomas. Discussion. Especially for patients with advanced stages of NSCLC, EGFR mutation status is necessary for treatment stratification. Our results show that the guidelines were followed increasingly over time for patients diagnosed with NSCLC at the Vestfold Hospital Trust. The establishment of interdisciplinary meetings has improved the diagnostic routines.